The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1093/ntr/ntv227
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Exposure During Pregnancy Results in Persistent Midline Epithelial Seam With Improper Palatal Fusion

Abstract: Introduction: Nonsyndromic cleft palate is a common birth defect (1:700) with a complex etiology involving both genetic and environmental risk factors. Nicotine, a major teratogen present in tobacco products, was shown to cause alterations and delays in the developing fetus. Methods: To demonstrate the postpartum effects of nicotine on palatal development, we delivered three different doses of nicotine (1.5, 3.0, and 4.5 mg/kg/d) and sterile saline (control) into pregnant BALB/c mice throughout their entire pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…The dose of 3 mg/kg/d of nicotine and the Balb/C strain were widely used to establish the PNE model for representing prenatal cigarette smoke exposure [ 30 – 32 ]. The 3 mg/kg/d dose of nicotine used in this study could equate to a moderate smoker during pregnancy (exposure to 6–8 cigarettes per day) [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dose of 3 mg/kg/d of nicotine and the Balb/C strain were widely used to establish the PNE model for representing prenatal cigarette smoke exposure [ 30 – 32 ]. The 3 mg/kg/d dose of nicotine used in this study could equate to a moderate smoker during pregnancy (exposure to 6–8 cigarettes per day) [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…It readily crosses the placenta and is concentrated in the fetal compartment (Luck, Nau, Hansen, & Steldinger, 1985) where it binds to nicotinic acetylcholine receptors that are widely expressed throughout the fetal nervous system, lungs, and other fetal tissues (Hellström-Lindahl, Gorbounova, Seiger, Mousavi, & Nordberg, 1998;Wongtrakool, Wang, Hyde, et al, 2012). Both human and animal pregnancy exposure studies show nicotine to be a developmental toxicant (Lin, Yon, Jung, et al, 2012;Ozturk et al, 2016;Schneider, Bizarro, Asherson, & Stolerman, 2010;Wickström, 2007) that is capable of interfering with normal neurotransmitter function, resulting in apoptosis and mitotic abnormalities (Slotkin, 2008;Wickström, 2007;Zhao & Reece, 2005), inducing lung (Maritz & Harding, 2011) and neurodevelopmental abnormalities (Dwyer, Broide, & Leslie, 2008;Slotkin, Seidler, Qiao, et al, 2004), and causing genotoxic effects in human fetal cells in vitro (Demirhan et al, 2011). A recent review of extant human and animal research concerning the developmental toxicity of nicotine concluded that "….nicotine contributes critically to adverse effects of gestational tobacco exposure" (England et al, 2017).…”
Section: Nicotine--a Developmental Toxicantmentioning
confidence: 99%
“…As cigarettes are known to be one of the most common teratogens [112], a number of serious obstetric complications arise with cigarette smoke exposure during pregnancy [113]. Approximately 10% of pregnant women in the US smoke, thereby exposing nearly 400,000 fetuses yearly to tobacco specific toxins [114].…”
Section: Health Outcomes and Comorbiditiesmentioning
confidence: 99%
“…Approximately 10% of pregnant women in the US smoke, thereby exposing nearly 400,000 fetuses yearly to tobacco specific toxins [114]. Exposure to smoke during pregnancy has been demonstrated to increase the likelihood of congenital limb deficiencies [115], congenital heart defects [116], orofacial clefting [112], and many other developmental abnormalities. Active smoking has long been considered a teratogenic agent that increases the risk of premature birth, but recent data shows that 22%–30% of nonsmoking pregnant women exposed to SHS are also at risk [117].…”
Section: Health Outcomes and Comorbiditiesmentioning
confidence: 99%